Testing of statcom model in IEEE 0 bus power system netwotk using PSCAD and MATLAB - Siti Nur Baizura, Abu Bakar (2010)
Power utilities have facing challenges due to increase load demands caused by rapid industries growth over years. One of the problems is the voltage instability in power system. Voltage stability is the ability of the system to maintain the voltage magnitude under normal condition and also under heavy stressed condition. Voltage instability is the power system that did not have the ability to meet reactive power demand. This will lead to a voltage collapse in the system. This project will present the performance of STATCOM installation in nine bus test system. A load flow analysis is conducted in order to obtain the power flow magnitudes, voltage levels and power losses in the distribution system. In addition, this project is to study the effectiveness of STATCOM by injecting at the critical location bus in the system. Thus, STATCOM that acts as a controller will regulate the terminal voltage and correcting the fault in transmission line of power system network.